Clinical outcomes, Kadish-INSICA staging and therapeutic targeting of somatostatin receptor 2 in olfactory neuroblastoma. (February 2022) - Lechner, Matt; Takahashi, Yoko; Turri-Zanoni, Mario; Liu, Jacklyn; Counsell, Nicholas; Hermsen, Mario; Kaur, Raman Preet; Zhao, Tianna; Ramanathan, Murugappan; Schartinger, Volker H.; Emanuel, Oscar; Helman, Sam; et al.
Abstract: Introduction: Olfactory neuroblastoma (ONB) is a rare cancer of the sinonasal region. We provide a comprehensive analysis of this malignancy with molecular and clinical trial data on a subset of our cohort to report on the potential efficacy of somatostatin receptor 2 (SSTR2)-targeting imaging and therapy. Methods: We conducted a retrospective analysis of 404 primary, locally recurrent, and metastatic olfactory neuroblastoma (ONB) patients from 12 institutions in the United States of America, United Kingdom and Europe. Clinicopathological characteristics and treatment approach were evaluated. SSTR2 expression, SSTR2-targeted imaging and the efficacy of peptide receptor radionuclide therapy [PRRT]( 177 Lu-DOTATATE) were reported in a subset of our cohort (LUTHREE trial; NCT03454763 ). Results: Dural infiltration at presentation was a significant predictor of overall survival (OS) and disease-free survival (DFS) in primary cases (n = 278). Kadish-Morita staging and Dulguerov T-stage both had limitations regarding their prognostic value. Multivariable survival analysis demonstrated improved outcomes with lower stage and receipt of adjuvant radiotherapy. Prophylactic neck irradiation significantly reduces the rate of nodal recurrence. 82.4% of the cohort were positive for SSTR2; treatment of three metastatic cases with SSTR2-targeted peptide-radionuclide receptor therapy (PRRT) in the LUTHREE trial was well-tolerated and resulted in stable disease (SD). Conclusions: This study presents pertinent clinical data from the largest dataset, to date, on ONB. We identify key prognostic markers and integrate these into an updated staging system, highlight the importance of adjuvant radiotherapy across all disease stages, the utility of prophylactic neck irradiation and the potential efficacy of targeting SSTR2 to manage disease. Highlights: Dural infiltration is prognostic and integrated into the Kadish-INSICA staging system (International Network for Sinonasal Cancer and Skull Base Tumours (www.insica.org). Adjuvant radiotherapy is beneficial across all stage groups, including early stage. Prophylactic neck irradiation prevents neck nodal recurrence. 82.4% express Somatostatin Receptor 2 (SSTR2) protein which can be used for SSTR2-targeted imaging. SSTR2-targeted peptide receptor radionuclide therapy is useful in metastatic disease.